VARIATION OF CUTTING PARAMETERS IN THE PROCESS OF TURNING AISI 4340 STEEL ON SURFACE ROUGHNESS - M. Sobron Yamin Lubis; Erwin Siahaan; Steven Darmawan; Adianto Adianto; Ronald Ronald (Universitas Mercu Buana, 2019)
In the metal machining process, cutting speed and feed rate are cutting parameters that affect the surface quality of the workpiece produced. The use of improper cutting parameters can cause the workpiece surface to be rough, and the cutting toolage to be shorter. This study was conducted to determine the effect of cutting parameters and the use of carbide tools on the surface roughness of metal steel workpieces. The research was carried out using the experimental method of AISI 4340 steel metal workpiece turning using cutting tool coated. Five variations of cutting speed used are: 140 m/min, 150 m/min, 160 m/min, 170 m/min, 180 m/min and three variations in feed rate: 0.25 mm/rev, 0.3 mm/rev, 0.35 mm/rev. After the turning process, the surface roughness of the workpiece is measured using a surface tester. From the results of the study, it was found that the surface roughness value was directly proportional to the feed rate and inversely proportional to the cutting speed. The smallest surface roughness value is 9.56 μm on cutting speed 180 m / min, and feed rate is 0.25 mm/rev.